The interaction between speech intelligibility task and non-auditory tasks - Kocinski, Jedrzej (Speech communication, 2015)
•A very sensitive method of speech intelligibility measurement was used.•The influence of non-auditory task on speech intelligibility was not noticed.•The influence of speech task on non-auditory task performance was noticed.•The results confirmed the cross-modal perceptual load effect. Many research on various aspects of speech perception and intelligibility has been conducted so far. However, the ability of human mind to perform multiple tasks simultaneously is still a challenging topic. Perceptual load theory states that people first decide what activity is most important after which available perceptual resources are allocated. Less important activities are conducted effectively only if remaining resources are sufficient. It should be emphasized that researchers studying divided attention focused mainly on activities requiring vision. This paper focuses on interaction between non-auditory tasks (distracters) and a speech intelligibility task. A very sensitive method based on speech reception threshold (SRT) measurement was used instead of standard speech intelligibility determination. This sensitivity is a result of a very steep psychometric function (ipso facto small standard deviation) which is not possible to achieve for standard methods. Therefore, this property can be used to investigate even slight impact of external conditions on speech perception. Two experiments examining the interactions between these two tasks were conducted. Despite the use of such sensitive method, in none of the experiments speech intelligibility decreased due to distracter. However, the percentage of correct responses to the distracter when subjects were performing speech intelligibility tests decreased compared to the situation when they focused only on the distracter.